First record of Lilioceris lilii in Greece - Papadoulis, Georgios Th.; Tsagkarakis, Antonios E. (ENTOMOLOGIA HELLENICA, 2012)
On May 2007, the lily beetle Lilioceris lilii (Scopoli) (Coleoptera: Chrysomelidae) was recorded for the first time in Greece. Its occurrence was observed on scarlet martagon lily and martagon lily plants at Fylaktí, Karditsa. Information on its morphology, biology and distribution is presented.